Japan's official development assistance : recent issues and future directions - Kawai, Masahiro, 1947- 1947- (Policy research working paper, 2001)
Japan can meet domestic and international challenges to its aid policies by developing a coherent national strategy for official development assistance, broadly designed to enhance partnership, effectiveness, accountability, and transparency